HIV-associated neurocognitive disorders: a changing pattern. (January 2011) - Simioni, Samanta; Cavassini, Matthias; Annoni, Jean-Marie; Hirschel, Bernard; Du Pasquier, Renaud A
Combination antiretroviral therapy has dramatically decreased the incidence of HIV-related mortality and serious opportunistic diseases, among which is HIV-associated dementia. However, minor forms of cognitive dysfunction have not disappeared and may even have increased in frequency. Aging of HIV + patients, insufficient penetration of antiretroviral drugs into the brain with continuous low-grade viral production and inflammation may play a role. A putative neurotoxicity of combination antiretroviral therapy is controversial. In this article, we will discuss these aspects, as well as clinical and pathophysiological features shared by HIV-associated neurocognitive disorders and other neurodegenerative diseases, especially Alzheimer's disease. This article will briefly summarize the current clinical trials on neuroprotective agents, and the management of patients with neurocognitive disorders will be discussed.